Implementation of Game Based Learning Model With Communication Oriented Method In Improving The Learning Outcomes of Students With Special Needs in grade IV of SD inpres Tamalanrea 6, Makassar city - Miftahul Hazizah; Syarifah Nur Fajrin; Musbaing Musbaing (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
This research was conducted from May 19 to June 21, 2025 at SD Inpres Tamalanrea 6 Makassar City by combining the Game Based Learning model and Communication Oriented method to train students' focus, speaking courage and social interaction. This research was applied to students with special needs who were in class IV The results show that the application of the GBL model combined with the Communication Oriented method is able to create a more active, enjoyable, and communicative learning atmosphere. ADHD students who previously experienced difficulty focusing began to show increased participation in learning activities, courage to communicate with teachers and peers, and the ability to complete assignments through educational games designed by teachers. However, the implementation of this model faces challenges in the form of limited resources, a lack of Special Assistant Teachers (GPK), a lack of adequate learning media, and less than optimal collaboration between teachers and parents. These findings indicate that the GBL model with a Communication Oriented approach is effective in improving the learning outcomes of students with special needs while creating a more supportive and inclusive learning environment.